The tow verbs (Wazara) and (Wadaa) in the Holy Quran: (Semantic grammatical study) - Widaa, Murtada (Al-Adab Journal, 2023)
This study aims in its entirety to reveal the uses of the verbs (wazara) and (wadaa) from grammatical and semantic perspectives in the Holy Quran, this is due to their participation in the same conjugation of verbs, the study followed the descriptive analytical and inductive approach, and it was presented in three axes: The tow verbs (Wazara) and (wadaa) in Arabic language, and the causes of their lack of conjugation of verbs and its grammatical and semantic uses in the Holy Quran. The study reached number of findings the most prominent of which are: The reasons that led to the lack of conjugation in the two verbs development and the linguistic uses of them. The verbs (Wazara) is mentioned in the present and command forms in line with the opinion of the grammarians, it comes in the present tense twenty –tow times and in the imperative form seventeen times, while the verb (Wadaa) mentioned tow times only; once in the imperative form and other in the past tense, objecting to the  opinion of the grammarians, when they said it comes in the form of the accusative and imperative, and their indication is to leave in general in all forms, one of the most prominent context in which the present tense is mentioned is form (Wazara): Remove the ambiguity, Threat and Intimidation , denial interrogation, Prayer and Despair, Rebuke and rebuke, Select the adjective, while the imperative verb it comes in the context of  threats in timidation and exaggeration of the outcome, entertainment and contempt, Guidance and Direction, while the verb (Wadaa) comes in entertainment to the past simple tense, Guidance and directions for imperative verb